Difference in nicotine metabolism as a potential factor causing disparities in tobacco consumption estimates by wastewater-based epidemiology - Min-Tz Weng; Kathryn J Steadman; Kelly Zhong; Maryam Al-Gharibeh; Qiuda Zheng; Phong K Thai (Health Sciences Review)
Wastewater-based epidemiology (WBE) can be used for estimating tobacco consumption at a population level. It involves analysing wastewater for the nicotine biomarkers cotinine (COT) and 3-hydroxycotinine (3HC). However, large discrepancies between WBE estimates for tobacco consumption compared to surveys and sales data have been reported. We hypothesise it could be partly related to genetic differences in CYP2A6 enzyme activity affecting COT and 3HC excretion. To review the use of COT and 3HC excretion factors within WBE calculations of tobacco consumption, a literature search for relevant articles was conducted using PubMed, EMBASE, CINAHL, PsycINFO, Web of Science, and Medline. A total of 34 papers were identified across the Americas, Oceania, Asian and European regions. In contrast to the other regions, 100 % of WBE cases involving East and Southeast Asian populations exhibited an underestimation of tobacco use when compared to surveys or sales data. The excretion factors used across all 34 papers had been derived from urine samples from predominantly White populations. People of Asian descent tend to have lower urinary concentrations of COT and 3HC than White populations due to slower CYP2A6 enzyme activity diverting nicotine metabolism towards non-CYP2A6 pathways. We show that using excretion factors that better represent Asian populations in WBE calculations can result in more accurate estimates of tobacco use. Measurement and use of excretion factors tailored to specific ethnic backgrounds can be expected to enhance the precision of WBE analysis.